1964
DOI: 10.1149/1.2426000
|View full text |Cite
|
Sign up to set email alerts
|

Steel Corrosion Mechanisms

Abstract: This paper summarizes what is known regarding the reaction of steel in high-temperature water as affected by sodium hydroxide additions and presents results of a detailed study of the reaction of 15% sodium hydroxide at 316~ by the hydrogen effusion method. The corrosion rates are correlated with microscopic study of the growth and breakdown of the protective magnetite films. It is shown that two different corrosion-rate-governing mechanisms are involved prior to the onset of pitting: a large decrease of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1966
1966
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The definition of quantities and the method of estimation are as follows: First, the sum of the amount of Fe ions in the oxide (W F ) and the amount of Fee , ions dissolved into the water (W 0 ) is the total amount of iron (6) autoclave (type 316), (7) heating system, (8) sample, (9) thermocouple system, (10) cooler, (11) pressure gauge, (12) filter, (13) leak valve, (14) piping system (type 316).…”
Section: Corrosion Rate Measurementmentioning
confidence: 99%
“…The definition of quantities and the method of estimation are as follows: First, the sum of the amount of Fe ions in the oxide (W F ) and the amount of Fee , ions dissolved into the water (W 0 ) is the total amount of iron (6) autoclave (type 316), (7) heating system, (8) sample, (9) thermocouple system, (10) cooler, (11) pressure gauge, (12) filter, (13) leak valve, (14) piping system (type 316).…”
Section: Corrosion Rate Measurementmentioning
confidence: 99%
“…Research initiated by Potter (1) in England and Bloom (2) in the United States has shown that the morphology of iron oxide films generated on steel by attack of high temperature NaOH solution is apparently dependent on the physical system employed. Static corrosion tests at these two laboratories using alkali solutions of similar composition and run at the same temperatures produce oxide films which are chemically the same (Fe304), but structurally different.…”
mentioning
confidence: 99%
“…In recent years (1)(2)(3)(4)(5)(6), studies h a v e been made of the growth of protective magnetite films on mild steel in alkaline solutions at typical operating temperatures in order to establish their properties and to throw some light upon the occasional circumstances in which they lose their protective character and produce a rapid pitting attack.…”
mentioning
confidence: 99%